Analisis Penggunaan Media Bimbingan dan Konseling pada Pemberian Layanan Informasi - Reni Sinta Dewi (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2023)
Guidance and Counseling as an important part of the world of education has an important contribution in molding the character of students as mandated by the Law. Advances in technology have motivated Guidance and Counseling teachers to create attractive media in providing information services as a service in guidance and counseling. The purpose of this study is to analyze the effectiveness of the use of media in information services. The research method is critical review using 10 articles from national and international journals through the Google Scholar page with a range of 2018-2023. The research results obtained are the use of guidance and counseling media has a positive impact on providing information services. Thus, these results are expected to be able to motivate guidance and counseling teachers to improvise in making guidance and counseling media.